Saint Francis, Pope Francis : a common vision - Loehr, Gina.; Giambrone, Al.; Morris, Jonathan, 1972- (Cincinnati, Ohio : Servant Books, published by Franciscan Media, 2014)
The first major decision of our new Holy Father's pontificate was choosing his papacy's patron. In taking the name of Francis, the pope indicated his desire to imitate the holy man from Assisi. But who was St. Francis, and what does his patronage mean for the newest successor of St. Peter? St. Francis was uniquely dedicated to being an authentic image of Christ to the world. The choice to follow Francis is ultimately a choice to follow Christ. Our Holy Father's decision to align himself with St. Francis therefore implies a desire to keep himself and his authority rooted in Christ. In this book, Gina Loehr examines five loves that characterized St. Francis's relationship with Christ: love of the church, love of the cross, love of peace, love of the poor, love of humility. Each chapter will begin with a scriptural reflection on one of these five loves in the life of Christ, followed by examples from the life of St. Francis, and finally with an examination of how Pope Francis has demonstrated his commitment to that particular gospel value. Relevant church teaching as well as questions for reflection will help readers discern how to incorporate these loves into their own lives. -- Provided by publisher.
Loving Christ, living the gospel -- Humility -- Charity -- The church -- Peace -- Joy.
Includes bibliographical references (pages 116-125).
Description based on print version record.
Keywords: Francis, -- of Assisi, Saint, -- 1182-1226.; Francis, -- Pope, -- 1936-; RELIGION / Institutions & Organizations; Electronic books